1994
DOI: 10.2337/diab.43.5.656
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Teratogenesis: In Vitro Evidence for a Multifactorial Etiology With Little Contribution From Glucose Per Se

Abstract: To determine the extent to which elevated glucose and 3-hydroxybutyrate (3OHB) concentrations contribute to the embryotoxic properties of diabetic serum, we tested the effects of serum from untreated or acutely insulin-treated diabetic rats on the development of mouse embryos during neurulation in vitro. Male Sprague-Dawley rats (n = 143) with streptozocin-induced diabetes for 1 week received infusions of insulin (n = 105) or saline (n = 38) for up to 120 min. The insulin-infused animals were exsanguinated whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…Experimental studies in vivo and in vitro have suggested that glucose and b -hydroxybutyrate cause growth retardation and malformations in rodent embryos [4][5][6]. In an earlier study we showed that serum from insulin-treated diabetic rats is teratogenic despite normalisation of glucose and b -hydroxybutyrate concentrations [7], in line with similar results by Buchanan et al [8]. These studies support the notion of a multifactorial aetiology of embryonic dysmorphogenesis in diabetic pregnancy [9,10].…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Experimental studies in vivo and in vitro have suggested that glucose and b -hydroxybutyrate cause growth retardation and malformations in rodent embryos [4][5][6]. In an earlier study we showed that serum from insulin-treated diabetic rats is teratogenic despite normalisation of glucose and b -hydroxybutyrate concentrations [7], in line with similar results by Buchanan et al [8]. These studies support the notion of a multifactorial aetiology of embryonic dysmorphogenesis in diabetic pregnancy [9,10].…”
supporting
confidence: 90%
“…On the other hand, culturing embryos in the same glucose concentration (30 mmol/l) in diabetic (50 MD) serum yielded further decreased embryonic size compared with culture in normal serum. This finding indicates the presence of teratogenic components in diabetic serum other than the high glucose concentration [7,8].…”
Section: Discussionmentioning
confidence: 75%
“…These data suggest similarities between the teratogenic actions of several specific teratogenic substances and maternal diabetes mellitus. The mechanisms for diabetic teratogenicity are perhaps the least well understood, probably due to the multitude of interacting teratogenic substances in diabetes mellitus [40,41,42]. Further insight in the teratogenic actions of maternal diabetes could therefore also cross-fertilise the understanding of other teratogens.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the transaminated product of leucine, a-keto-isocaproic acid, is teratogenic in rat embryo culture at a concentration as low as 3 mmol/L (23). In a recent study, Buchanan et al (48) reported that the teratogenic potential of serum from diabetic rats was dependent on other factors in addition to the elevated levels of glucose. The experimental finding of the teratologic potential of diabetes-associated metabolites, in addition to glucose, agrees…”
Section: Discussionmentioning
confidence: 99%